Biomechanical analysis of badminton net kills upper limb movements between forehand and backhand grips - Pan, K. M.; Tsai, L. C.; Chang, C. H.; Huang, K. S. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume II: Bio-Mechanics and Sports Engineering., 2008)
The purpose of this study was to analyze the kinematical variables of the badminton players when they were performing forehand and backhand net kill strokes. Eight collegiate elite male badminton players in Taiwan (age 20yrs, high 176cm, weight 71kg) were served as the subjects. In this study, we were interested in analyzing the motions from the phase of preparation while the center of mass (COM) went down to the lowest position to the point of making contact with the shuttlecock. Ten Vicon MX-13+ cameras (Vicon, Oxford, UK, 250Hz) were used to record the 3D kinematics dula and calculatcd by Vicon Nexus 1.1 system. The nonparametric statistical test of Wilcoxon matched-paired signed-rank test between forehand and backhand net kills for the diffcrences in kinematies at a .05 significant level. The results showed that there were no significant differences between forehand and backhand net kills in the initial shuttle velocity, the initial shuttle angle, the contact height and the movement duration time. The distance from the contact point to COM, the backhand net kill was greater than the disiance of forehand in the saggital orientation. The dominant upper limb joint angle at the contact point, the forehand net kill was greater than the hackhand's in the extension and abduction shoulder angle. The forehand net kill stroke was greater than the wrist adduction angle of backhand net kill stroke. The player raised their upper arms more to perform the forehand than backhand net kills. From the results of the upper limb joint angular velocity, the subjects manipulate the shoulder rotation to perform the forehand net kill, but they exert the wrist joint to perform the backhand net kill. The backhand net kill seemed more relate with the kinetics chain rule. The movement performance effect was very similar between forehand and backhand net kills, but the strategy of the forehand and backhand net kill movement was different.